2018 IEEE International Symposium on the Physical and Failure Analysis of Integrated Circuits (IPFA) 2018
DOI: 10.1109/ipfa.2018.8452604
|View full text |Cite
|
Sign up to set email alerts
|

Descrambling of Embedded SRAM Using a Laser Probe

Abstract: Understanding the organization of memory is a mandatory first step in various fields of applications such as failure analysis, defect localization, qualification and testing of space electronics, and security evaluation. For the last category, localization of specific addresses may be used for content estimation or encryption key recovery, with several techniques being reported for this task. In this paper, we discuss the application of laser probing for descrambling memory embedded in 8 bits microcontrollers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…6, the data 0xAA on even addresses and 0x55 on odd addresses. Prior work [24] had shown that data were stored by the weight of the bits. Instead of four addresses, eight consecutive addresses share the same wordline signal.…”
Section: Application and Resultsmentioning
confidence: 99%
“…6, the data 0xAA on even addresses and 0x55 on odd addresses. Prior work [24] had shown that data were stored by the weight of the bits. Instead of four addresses, eight consecutive addresses share the same wordline signal.…”
Section: Application and Resultsmentioning
confidence: 99%
“…Furthermore, a more precise technique that security evaluation labs would typically choose, is laser fault injection. An attacker can use laser beams to probe the memory revealing its content without changing it [23]. A laser FIA can also cause the bypass of a secure boot process and the authentication check step, or to recover the encryption key [17].…”
Section: E Optical Fault Injectionmentioning
confidence: 99%
“…On one hand, there are works using an inexpensive camera flash to cause random faults [41], on the other, an attacker can use a nanofocused X-ray beam to target a single transistor [16]. Moreover, it was shown that with the usage of lasers it is possible to probe the memory without changing it, which can reveal its content [42]. Therefore, the practicality range varies greatly for this class of attacks.…”
Section: B Optical Fault Injectionmentioning
confidence: 99%